ECONOMIC EMPOWERMENT AND FOOD SECURITY: A SYSTEMATIC LITERATURE REVIEW FROM A DEVELOPMENT ECONOMICS PERSPECTIVE - Zakaria, Junaiddin; Ghifari, Muhammad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to analyze Bibliometrics on Economic Empowerment and Food Security from a Development Economics Perspective. The method used is qualitative research with a literature study approach, where the data found and analyzed includes 99 documents obtained from the Scopus database. The analysis used VOSviewer to map and analyze the data. The analysis results show a global trend showing a significant increase in publications from 2018 to 2023, reflecting the growing interest and focus in Economic Empowerment and Food Security research from a Development Economics Perspective. The United States is the country that contributes the most research publications on this topic. In 2023, Anwar, S., Elum, Z.A., Gitaharie, B.Y., Handayani, D., Khan, M.T.I., Mayo Wilson, L.J., Omotayo, A.O., and Slotow, R. were the most productive authors, each contributing 2 documents. Research trends show an increasing focus throughout the decade, highlighting the importance of understanding and research efforts in addressing complex challenges related to economics and food security.